A planet in a polar orbit of 1.4 solar-mass star - Guenther, E. W.; Cusano, Felice; Deeg, Hans; Gandolfi, Davide; Geier, S.; Grziwa, S.; Heber, Ulrich; Tal-Or, Lev; Sebastian, D.; Rodle, F. (EPJ Web of Conferences, 2015)
Although more than a thousand transiting extrasolar planets have been discovered, only very few of them orbit stars that are more massive than the Sun. The discovery of such planets is interesting, because they have formed in disks that are more massive but had a shorter life time than those of solar-like stars. Studies of planets more massive than the Sun thus tell us how the properties of the proto-planetary disks effect the formation of planets. Another aspect that makes these planets interesting is that they have kept their original orbital inclinations. By studying them we can thus find out whether the orbital axes planets are initially aligned to the stars rotational axes, or not. Here we report on the discovery of a planet of a 1.4 solar-mass star with a period of 5.6 days in a polar orbit made by CoRoT. This new planet thus is one of the few known close-in planets orbiting a star that is substantially more massive than the Sun.
CRIS-Team Scopus Importer:2020-12-21